Helicopter theory - Johnson, Wayne, 1946- (Dover Publications, 1994)
Monumental text offers comprehensive, detailed coverage of every aspect of theory and design: elements of vertical flight, forward flight, performance, mathematics of rotating systems, rotary wing dynamics and aerodynamics, aeroelasticity, stability and control, more. Essential reading for those interested in design and development of vertical-flight aircraft. 189 illustrations. 1980 edition.